Degradation of dye wastewater using aerobic membrane bioreactor - Intan Diana, Yusof (2010)
Homemade textile industry is very famous in the East Coast of Peninsular Malaysia. Known locally as Batik Industries, they are traditionally inherited from generation to generation. The Batik Industry makes a big contribution to the economic growth due to high demands locally and from abroad. However, this industry produces wastewater which contributes to water pollution since it utilizes a lot of chemicals. Preliminary studies show that the wastewater from these homemade textile industries contains grease, wax, heavy metal, surfactant, suspended solid, and dyes (organic and inorganic). This study explores the use of aerobic membrane bioreactor processes to remove the suspended solid (mainly due to dyes in the painting and coloring processes) from wastewater of batik industry. Besides that, the effect of dye concentration (color), BOD and COD were studied based on it respect hydraulic retention time. Data on the flux and average values for each of the parameters studied were presented systematically. The results show that the dye concentration, BOD and COD the operating pressure was found to affect the process. The average flux was increased when the applied pressure was increased. The data collected could be used to improve the effectiveness of dye removal from the batik industry wastewater using membrane technology.